Addresses on Industrial Relations (1957 Series) - Tremblay, Louis-Marie (Relations industrielles / Industrial Relations, 1958)
The article reviews "Addresses on Industrial Relations (1957 Series)." Published by the Bureau of Industrial Relations, University of Michigan, Ann Arbor, Bulletin No. 25.